1978
DOI: 10.1007/bf02293646
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional scaling of nominal data: The recovery of metric information with alscal

Abstract: data analysis, data quantification, optimal scaling, catetorical data, nonmetric, Monte Carlo, euclidian,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

1980
1980
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
2
6
0
2
Order By: Relevance
“…Numerous previous Monte Carlo studies (e.g., Drasgow & Jones, 1979;Sherman, 1972;Young, 1970;Young & Null, 1978) have consistently found both the number of stimuli and the error level to have a significant effect on the degree of recovery, and Tables 2-5 suggest that this is also true here.…”
Section: Effects In the Main Studysupporting
confidence: 49%
See 1 more Smart Citation
“…Numerous previous Monte Carlo studies (e.g., Drasgow & Jones, 1979;Sherman, 1972;Young, 1970;Young & Null, 1978) have consistently found both the number of stimuli and the error level to have a significant effect on the degree of recovery, and Tables 2-5 suggest that this is also true here.…”
Section: Effects In the Main Studysupporting
confidence: 49%
“…Such data are obtained by taking the interpoint distancels (optionally with added error) from a known configuration and quantizing them into the required number of levels, an approach previously used by Young and Null (1978). The extreme case of quantization into binary dissimilarities is studied here.…”
mentioning
confidence: 99%
“…In addition to the usual linear transformations, ALSCAL permits ordinal and category-preserving transformations. A fairly large study by Young and Null (1978) showed that ALSCAL can perform well in recovering a known configuration if the level of measurement is known, and even if it is not, ALSCAL may be useful in helping to determine the level of measurement and to recover the underlying structure in the data.…”
Section: Demonstrationsmentioning
confidence: 97%
“…-A válaszadók a neuromarketing-kutatásokat a hagyományos kutatásokkal együtt használhatónak, mintsem azok helyettesítőinek tekintik. A fenti összegzés mellett a multidimenzionális skálázás segítségével a neuromarketinggel kapcsolatos változókból ALSCAL-eljárással (Young & Null, 1978) modellt alkottunk, az alacsony mintaszám okán kerülve a faktorelemzést. Az MDS alapját képező kérdés 13 állítást tartalmazott a neuromarketinghez kapcsolódó attitűdökről.…”
Section: Neuromarketing-ismeretek -Attitűdök -Szándékok -Egy Felmérésunclassified